Developing Malay cultural heritage areas as historical religious cultural tourism: A case study of Rantau Panjang village, Deli Serdang, Indonesia - Sinar, Tengku Mira Rozanna; Harahap, R. Hamdani; Humaizi, Humaizi; Subhilhar, Subhilhar (Research Journal in Advanced Humanities, 2025)
This research aims to analyze the development strategy of the cultural heritage area in Rantau Panjang Village and identify its development model as a sustainable religious, historical tourist attraction in Deli Serdang Regency, Indonesia. The methodology used is descriptive qualitative, where data is obtained through field information collection by conducting interviews with twelve key informants and documentation studies. The collected data were then analyzed and interpreted, presented in tabular format and visual representation, with the help of NVivo software to process qualitative data. The results show that advancing the cultural heritage area in Rantau Panjang Village is a multifaceted endeavour that requires substantial dedication from various stakeholders. With the implementation of appropriate strategies and proactive community involvement, this cultural heritage area has the potential to develop into an attractive and sustainable cultural tourism destination. A successful model for developing this area requires careful planning, strong collaboration between various parties, and active community participation. With a comprehensive and sustainable methodology, this area can be used as an example of Indonesia's cultural heritage conservation and historical tourism development. The contribution of this research provides a foundation for further development to preserve and promote cultural wealth and historical tourism in Indonesia.